PP.02.10: A GENETIC MARKER OF HYPERURICEMIA PREDICTS CARDIOVASCULAR EVENTS IN A META-ANALYSIS OF THREE COHORT STUDIES IN HIGH RISK PATIENTS. (June 2015) - Testa, A.; Prudente, S.; Spoto, B.; Sanguedolce, M.C.; Parlongo, R.M.; Tripepi, G.; Mallamaci, F.; Leonardis, D.; Federici, M.; Trischitta, V.; Zoccali, C.
Abstract : Objective: Whether hyperuricemia is causally implicated in atherosclerotic complications is one among of the most vexed questions in CV medicine and there is no randomized trial based on clinical end-points testing the hypothesis that reducing serum uric acid (UA) may reduce CV events in high risk pts. The strongest genetic marker of UA levels, the rs734553 SNP in the GLUT9 urate transporter gene, predicts progression to kidney failure in CKD patients and associates with systolic BP and carotid intima media thickness. Figure. No caption available. Design and method: We used the risk allele of this genetic polymorphism as an unconfounded research tool to explore the link between UA and CV events (Mendelian randomization) in a meta-analysis of 3 cohorts enrolling high risk patients. The three cohorts included 755 G2-G5 CKD pts(MAURO);353 pts with type-2diabetes and coronary artery disease (GHS) and 119 pts with severe coronary heart disease and MI (TVAS). The major clinical end point was a composite end point including CV death or nonfatal stroke, nonfatal MI. Genotyping was performed by RT-PCR. The meta-analysis was performed by the random effects approach. Results: During follow-up, 117 CV events occurred in MAURO, 72 in GHS and 33 in TVAS. In separate analyses in the 3 cohorts, the incidence of CV events was higher in patients with the rs734553 risk allele (TT/GT) than in those without (GG patients) and the HR in the three cohorts was similar with no heterogeneity (I2 = 0.01) among the three cohorts (fig.1). The meta-analytical estimate in the three cohorts (total patients number = 1227;total CV events = 222) of the risk for cardiovascular events in TT/GT patients was twice higher (pooled HR:2.04, 95%CI:1.11–3.75, P = 0.02) than in GG homozygotes. Conclusions: In a meta-analysis of 3 cohorts formed by patients at high cardiovascular risk, the T allele of the rs734553 polymorphism of the GLUT9 gene predicts a doubling in the risk for incident cardiovascular events. This meta-analysis is coherent with previous studies linking the same polymorphism with the risk of kidney failure, hypertension and atherosclerosis. Findings in this study supports the hypothesis of a causal role of hyperuricemia in cardiovascular disease in high risk conditions.